2000
DOI: 10.1038/sj.bjp.0703554
|View full text |Cite
|
Sign up to set email alerts
|

On the in vitro vasoactivity of bile acids

Abstract: 1 We compared the vasorelaxant action of nine dierent bile acids and correlated their vasorelaxant activity with their individual indices for hydrophobicity or lipophilicity. 2 Vasorelaxant activity correlated with the relative lipid solubility of bile acids with lipophilic bile acids exhibiting the greatest vasorelaxant activity with modest to no vasorelaxant activity exhibited by hydrophilic bile acids. 3 We also investigated whether bile acid-induced vasorelaxation is mediated by antagonism of a prototypal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 57 publications
2
24
2
1
Order By: Relevance
“…Among naturally occurring bile acids, the monohydroxylated LC is remarkably effective in increasing vascular myocyte BK channel activity (4), which is consistent with the powerful smooth muscle relaxant properties of hydrophobic bile acids (15). We have recently demonstrated that LC-induced vasodilation is largely endotheliumindependent, and blunted after genetic ablation of KCNMB1 (6).…”
mentioning
confidence: 68%
“…Among naturally occurring bile acids, the monohydroxylated LC is remarkably effective in increasing vascular myocyte BK channel activity (4), which is consistent with the powerful smooth muscle relaxant properties of hydrophobic bile acids (15). We have recently demonstrated that LC-induced vasodilation is largely endotheliumindependent, and blunted after genetic ablation of KCNMB1 (6).…”
mentioning
confidence: 68%
“…It is well acknowledged that BAs can solubilize membranes extracellularly by promoting cholesterol and phospholipid clearance [6, 14]. So we hypothesized that BAs disturbed caveolae intactness on ECs membranes through diminishing cholesterol which induced vasorelaxation by facilitating eNOS phosphorylation and NO production.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, hydrophobic BAs exhibit greater effect than hydrophilic ones, underlying which multiple mechanisms have been proposed [6]. For example, deoxycholic acid (DCA) or chenodeoxycholic acid (CDCA) prevents activity of contractile surface membrane receptors through lipid peroxidation [6]. CDCA promotes nitric oxide (NO) production in vascular endothelial cells (ECs) by interaction with TGR5, a plasma membrane receptor [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some of these subjects, systemic circulating levels of bile acids may reach more than 100 M (Ostrow, 1993). It has even been speculated that bile acids may serve as endogenous vasodilators (Bomzon and Ljubuncic, 1995), and bile acid relaxation of vascular smooth muscle seems to be caused by steroid actions on the smooth muscle itself (Ljubuncic et al, 2000). It is remarkable that the vasoactive properties of bile acids have not been tested in small, resistance-size arteries that develop myogenic tone; these arteries are critical to determining pressure and blood flow.…”
mentioning
confidence: 99%